1999
DOI: 10.1149/1.1391769
|View full text |Cite
|
Sign up to set email alerts
|

Cathode of LiMg y Mn2 − y  O 4 and LiMg y Mn2 − y  O 4 − δ Spinel Phases for Lithium Secondary Batteries

Abstract: To improve the cycle performance of LiMn2O4 false(normalFdtrue3¯mfalse) as the cathode of 4 V class lithium secondary batteries, the cathode properties of the quaternary cubic spinel phases LiMgyMn2−yO4 synthesized at 750°C were examined. Although the cycle performance of the LiMgyMn2−yO4 was improved by the substitution of Mg2+ for Mn3+ in the octahedral sites, the first discharge capacity was reduced considerably compared with that of the parent LiMn2O4 . In order to compensate for the theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
47
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 15 publications
3
47
0
Order By: Relevance
“…It is therefore very important to stabilize the cubic spinel structure. Various divalent and trivalent ions, which make the structure more stable, have been tried as dopants by different groups [8][9][10]. Experimentally, among the various possible dopants chromium and magnesium have been studied extensively [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore very important to stabilize the cubic spinel structure. Various divalent and trivalent ions, which make the structure more stable, have been tried as dopants by different groups [8][9][10]. Experimentally, among the various possible dopants chromium and magnesium have been studied extensively [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the amount of substituent ions within the spinel structure should be carefully adjusted in order to obtain higher specific capacities around the 4 V potential window. Several reports have also confirmed that substituting metal ions such as Cr, Co or Ni less than 0.2% will significantly improve the cyclability . Wu et al have reported that the substitution of Cr ions in LiMn 2‐x Cr x O 4 results in a conversion of Cr 3+ to Cr 6+ for x > 0.2.…”
Section: Introductionmentioning
confidence: 93%
“…Several reports have also confirmed that substituting metal ions such as Cr, Co or Ni less than 0.2% will significantly improve the cyclability. 16 Electron paramagnetic resonance and X-ray diffraction studies have shown that x Cr = 0.06 samples have significantly suppressed the Jahn-Teller distortion. The results clearly indicates that the increment above x Cr = 0.06 will decrease the first discharge capacity gradually since Cr ions will not oxidize around 4 V. 21 Moreover, surface coatings have been widely employed to prevent micro-strain during cycling and reduce capacity fading in LMO.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Er ion has a larger bonding energy (615 kJ/mol) in ErO 6 octahedra compared to the Mn ion in MnO 6 octahedra (402 kJ/mol), which is another reason for the improved capacity retention of LiMn 2 − x Er x O 4 electrodes. Hayashi et al thought that the larger the bonding energy in the octahedral MO 6 sites, the smaller the lattice parameter of the spinel oxide [20]. Accordingly, the increase of the bonding energy for the Er-substituted spinel would cause a shrinkage of the lattice, which could stabilize the spinel LiMn 2 O 4 structure.…”
Section: Introductionmentioning
confidence: 99%